Colonial Hospital, Port of Spain, Trinidad. B.W.I. - (:unkn) unknown (James Book Store, 2009)
Photo of the Colonial Hospital with a view of the flowers and trees on the grounds of the building.
Colour: Green, Red, Brown and Grey; Style: Landscape; Other: Unbordered; Divided
Keywords: Trinidad and Tobago; Postcards; Hospitals--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago